Daytime, tidal amplitude and protected areas influence movements and habitat use on mudflats of wintering black-tailed godwits. (5th May 2022) - Jourdan, Clément; Fort, Jérôme; Pinaud, David; Delaporte, Philippe; Hérault, Thomas; Jankovic, Marko; Jomat, Loïc; Lachaussée, Nicolas; Pineau, Philippe; Robin, Frédéric; Rousseau, Pierre; Bocher, Pierrick
Abstract: Understanding environmental factors underlying animal foraging distribution is of major importance in defining priority conservation actions. During their wintering stage, most shorebirds depend on intertidal areas, as foraging grounds, and on supratidal areas, as high tide roosts. The accessibility of foraging areas and food resources is thus limited, and most wintering shorebirds have to forage whenever mudflats are available, both day and night, to fulfil their daily energetic demands. However, current knowledge of shorebirds' spatio-temporal use of foraging habitats is often restricted to the daylight period. In that context, we investigated the spatial distribution and habitat selection of wintering black-tailed godwits Limosa limosa islandica, during both the day and night, and in relation to the environmental characteristics. We equipped wintering black-tailed godwits at two different sites on the Pertuis Charentais (Atlantic French coast) with miniaturised GPS loggers. We then tested the hypothesis that godwits feed both during day and night, and show contrasting foraging behaviours and distribution in response to different visual capacities, prey availability, predation risks and human activities. The selection of feeding areas was highly variable according to nycthemeral periodicities, with little change in the habitat types selected. The estimated nocturnal surface of feeding areas were two times smaller than daytime ones, and located closer to the coastline. Moreover, birds largely foraged inside protected areas during the daytime, while most of them foraged outside at night. Finally, godwits with the smallest feeding home ranges stayed inside the Nature Reserves, during both day and night, while the others prospected outside the protected areas more often, preferentially at night. Highlights: Few studies examined behaviour of Shorebird at fine spatiotemporal scale. Our results highlighted nocturnal feeding areas two times smaller than daytime ones, and located closer to the coastline. Birds largely foraged inside protected areas during the daytime, while most of them foraged outside at night.